Notable women scientists - Proffitt, Pamela, 1966- (Detroit : Gale Group, 1999)
Biographical profiles of 500 women around the world who have made significant contributions to the field of science, from antiquity to the present.
Includes bibliographical references and indexes.
Keywords: Women scientists -- Biography -- Juvenile literature